2017
DOI: 10.1080/0267257x.2017.1377754
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning consumers: how videography can contribute to marketing knowledge

Abstract: Based on a review of the past thirty years of videographic research and outputs in the field of marketing, we highlight the key contributions that videography has made to the marketing literature and identify the key issues facing videographic research today. We develop a typology that identifies four ways that videography can contribute to theory development and verification, presenting new criteria for assessing academic videographies. We note that making theoretical contributions is one of the most difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 59 publications
(39 reference statements)
0
32
0
1
Order By: Relevance
“…Taking photos one-step further; video usage is also advocated as another method for exploring consumer perceptions of services marketing (Belk and Kozinets, 2005;Belk et al, 2018). Termed 'videography', the approach can be employed in a number of ways such as recording interviews and observations but can also be used by consumers to capture their own experiences (Kozinets and Belk, 2006).…”
Section: The Use Of Photographic Elicitation By Academic Researchersmentioning
confidence: 99%
“…Taking photos one-step further; video usage is also advocated as another method for exploring consumer perceptions of services marketing (Belk and Kozinets, 2005;Belk et al, 2018). Termed 'videography', the approach can be employed in a number of ways such as recording interviews and observations but can also be used by consumers to capture their own experiences (Kozinets and Belk, 2006).…”
Section: The Use Of Photographic Elicitation By Academic Researchersmentioning
confidence: 99%
“…Some tools, such as life narratives and consumer diaries (Roederer, 2012), or visual approaches through images and videos (Peñaloza, 1998;Belk and Kozinets, 2005;Belk et al, 2017) have also been used more often since the introduction of the experiential paradigm.…”
Section: Methodological Renewalsmentioning
confidence: 99%
“…Video-based research has the ability to capture the live interactions and dynamics of an experience. Lemke (2007: 40) suggested that video is "a space of visible and audible dynamic activity", which has temporal affordances and produces permanent and accessible observations of an experience, thus addressing the need for a dynamic approach to studying experience, and producing records that allow full immersion in the data for the purposes of analysis (Belk, Caldwell, Devinney, Eckhardt, Henry, Kozinets, & Plakoyiannaki, 2017). The multimodality of videography also provides a basis for translating the aforementioned tacit, aesthetic and embodied aspects of experience into elusive knowledge (Toraldo et al, 2016), by offering "a sense of understanding that is novel and interesting, evocative and emotionally engaging" (Belk et al, 2017: 3).…”
Section: Thatmentioning
confidence: 99%
“…Table 1, below, presents a comprehensive comparison of netnography, videography and screencast videography, highlighting the focus of each method, the opportunities they present, and their shortcomings. ******Insert Table 1 Here****** As such, screencast videography (SCV) is situated in the broader methodological realm as an extension of exploratory and observational research designs (Corbin & Strauss, 2014) and videographic forms of inquiry (Christianson, 2016;Toraldo et al, 2016;Lemke, 2007;Belk et al, 2017;Rokka et al, 2017). It could potentially follow a style of videographic netnography that focuses on the dynamism of digital experiences, live interactions and customer journeys in the form of recorded videographic observations within the digital realm.…”
Section: Thatmentioning
confidence: 99%